2021
DOI: 10.1002/smll.202103422
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Protein‐Encapsulated Ceria Nanorods for Visible‐Light Driven Hydrogen Production and Carbon Dioxide Reduction

Abstract: 1D rare earth‐based nanomaterials have attracted significant attention due to their excellent photo/electro‐catalytic performance. The corresponding challenge is how to synthesize shape and size‐controlled nanostructures in an easy scale‐up way. Herein, the authors present a facile one‐step strategy to design 1D multifunctional protein‐encapsulated cerium oxide nanorods (PCNRs) by utilizing bovine serum albumin as an efficient biotemplate. Remarkably, the PCNRs exhibit high chemical and interfacial adhesion sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 86 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…The synthetic method is simple and effective since only three raw materials are utilized in the synthesis process, the synthesis process is green without high temperature and pressure, and the synthetic method can be adapted to mass production. The formation of CeO 2 @BSA nanoclusters was characterized by UV–vis spectroscopy, which showed that the absorption peak around 330–340 nm corresponded to Ce–O bonding and that around 280 nm corresponded to BSA , (Supplementary Figure 1A). The size of CeO 2 @BSA could be regulated by different ratios of BSA/Ce 3+ (Supplementary Table 1, supplementary Figure 1B).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic method is simple and effective since only three raw materials are utilized in the synthesis process, the synthesis process is green without high temperature and pressure, and the synthetic method can be adapted to mass production. The formation of CeO 2 @BSA nanoclusters was characterized by UV–vis spectroscopy, which showed that the absorption peak around 330–340 nm corresponded to Ce–O bonding and that around 280 nm corresponded to BSA , (Supplementary Figure 1A). The size of CeO 2 @BSA could be regulated by different ratios of BSA/Ce 3+ (Supplementary Table 1, supplementary Figure 1B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Herein, nanoceria was synthesized by a convenient, green, and highly effective bovine serum albumin (BSA) incubation strategy, where BSA provided a spatial confinement effect for nanoparticle growth and preventing aggregation. BSA has been widely used to synthesize nanoparticles for neurological disorders. More importantly, the level of serum albumin decreases in depression patients and high serum albumin levels may provide protection against depression. Several key experiments have been performed in solution, in vitro , and in vivo to assess the ROS scavenging ability, BBB crossing capacity, metabolism, and cytotoxicity of BSA-incubated nanoceria (CeO 2 @BSA). The therapeutic effects of CeO 2 @BSA nanoclusters were determined using the chronic restraint stress (CRS)-induced depressive model, a more credible depression model to simulate human stress in life, compared with other inflammatory models such as the lipopolysaccharide (LPS)-induced one .…”
Section: Introductionmentioning
confidence: 99%
“…[ 16,17 ] Very recently, a few reports have also shown the potential of the supported rare‐earth atoms acting as the active centers for CO 2 photoreduction. [ 18–21 ] For example, single atomic Er, Dy, or La elements loaded on supports exhibited enhanced performance for CO 2 photoreduction compared with the corresponding rare‐earth free samples. [ 18–20 ] In these cases, the special 4f orbital characteristics of rare‐earth atoms facilitate the electron transfer during the reaction, rendering them as good active centers for CO 2 photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18–21 ] For example, single atomic Er, Dy, or La elements loaded on supports exhibited enhanced performance for CO 2 photoreduction compared with the corresponding rare‐earth free samples. [ 18–20 ] In these cases, the special 4f orbital characteristics of rare‐earth atoms facilitate the electron transfer during the reaction, rendering them as good active centers for CO 2 photoreduction. However, as loaded active centers, these rare‐earth‐based photocatalysts suffer from complex fabrication procedures, low loading amount, aggregation during the reactions, etc., which greatly hinders the development of rare earth elements in the field of CO 2 photoreduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation